Social change and marriage structure in Nigeria - Esiri, May Omogho (International research journal of management, IT and social sciences, 2021)
Marriage as a social institution has undergone changes in structure in contemporary Nigeria. Whether in simple or complex societies, social change is a universal phenomenon. In most cultural groups in indigenous Nigeria, marriage is usually an arrangement between two individuals. As a result there is pressure on the spouses to make the marriage a success bearing in mind the fact that any problem will usually affect both families and strain the otherwise cordial relationship between them. Again, polygyny commonly known as polygamy is the most practiced marriage system. However, the marriage structure in Nigeria today has not been the same. It is found in the name of modernization or civilization that a girl and a boy may decide to marry away from their parents’ place of residence and without their consent. Monogamous marriage is now increasingly encouraged and practiced. The paper thus examines the extent of social change in the Nigerian marriage structure.